2023
DOI: 10.1007/s12325-022-02421-w
|View full text |Cite
|
Sign up to set email alerts
|

TMPRSS6 as a Therapeutic Target for Disorders of Erythropoiesis and Iron Homeostasis

Abstract: TMPRSS6 is a serine protease highly expressed in the liver. Its role in iron regulation was first reported in 2008 when mutations in TMPRSS6 were shown to be the cause of iron-refractory iron deficiency anemia (IRIDA) in humans and in mouse models. TMPRSS6 functions as a negative regulator of the expression of the systemic iron-regulatory hormone hepcidin. Over the last decade and a half, growing understanding of TMPRSS6 biology and mechanism of action has enabled development of new therapeutic approaches for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…Since T-ASO showed increased hepcidin levels and reduced TfSat in healthy volunteers, we predicted that BT patients would improve splenomegaly and iron overload. 27 Based on this rationale, we investigated the effects of combining the two different treatment strategies to treat the distinct co-morbidities in BT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since T-ASO showed increased hepcidin levels and reduced TfSat in healthy volunteers, we predicted that BT patients would improve splenomegaly and iron overload. 27 Based on this rationale, we investigated the effects of combining the two different treatment strategies to treat the distinct co-morbidities in BT.…”
Section: Discussionmentioning
confidence: 99%
“…20,[22][23][24][25][26] TMPRSS6 is a transmembrane serine protease expressed in hepatocytes and has been identified as a negative regulator of the receptor complex that controls hepcidin transcription. 27 Our pre-clinical studies using TMPRSS6-ASO in a mouse model of BT-intermedia (Hbb th3/+ or th3/+) have shown that this approach improves anemia, lengthens RBC lifespan, reduces ERFE, hemichromes, reactive oxygen species (ROS), and ameliorates splenomegaly. 20,22,26 Clinical trials testing TMPRSS6 inhibition in healthy volunteers (NCT03165864) showed reductions in iron availability for RBC production, as evidenced by lowered transferrin saturation (TfSat), hemoglobin (Hb), and hematocrit (Hct) measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, another clinical trial on hepcidin agonists (PTG-300) for polycythemia vera effectively replaced phlebotomy for the hematocrit control. ( 89 ) N -acetylgalactosamine-modified antisense oligonucleotide, which targets TMPRSS6 mRNA (Sapablursen), has been analyzed in clinical trials in patients with non-transfusion-dependent β-thalassemia (NCT04059406) and is currently being assessed in an ongoing clinical study in patients with polycythemia vera (NCT05143957). Further studies on iron metabolism are required to develop novel therapeutic approaches.…”
Section: Hepcidin-ferroportin Axismentioning
confidence: 99%
“…4,5 Clinical trials testing several novel iron restriction compounds in β-thalassemia patients have been terminated due to failure in meeting the primary endpoints, halting further clinical development for the disease. 2,6 While hemoglobin increase was, in most of the cases, the primary endpoint and, indeed, the desired goal of such trials, this might have not been the right endpoint of these studies at this stage, until finding suitable dosing. These molecules are, in fact, primarily iron restriction compounds and, according to the degree of iron restriction achieved, hemoglobin values might be improved in light of reduced iron-toxicity on erythroid precursors, or decreased in case of continuously limited access of the erythron to iron, resulting in iron-restricted erythropoiesis.…”
mentioning
confidence: 99%